CRIMINALIZATION OF POLYGAMY - Rahmi Nurtsani; Yuli Kasmarani (Universitas Islam Negeri Raden Fatah Palembang, 2023)
There are many cases that occur within the scope of family law, especially in marriage. One of the cases that is most highlighted in the community because of its sensitive nature is polygamy. Therefore, this study will explain how polygamy is one of the triggers for criminal acts and causes the perpetrators to receive sanctions or punishments. This research methodology uses library research which is a qualitative research, namely research by examining and analyzing data from library sources, either in the form of books, papers, journals and others related to polygamy and all its legal consequences. The conclusions obtained in this paper are that the criminalization of polygamy here is understood as an attitude that categorizes the practice of polygamy as a criminal act, which is threatened with certain forms of crime, both imprisonment and fines. The legal provisions in force in the Republic of Indonesia do not prohibit polygamous marriages, but also do not allow them to be free without rules. The Republic of Indonesia regulates it with strict and clear terms and conditions as stated in the provisions of the applicable laws and regulations, KUHP, UU PKDRT, UU No.1/1974 which also applies very strict conditions for the practice of polygamy, especially the fulfillment of physical and spiritual needs for children and wives who are not the only one. As data from KOMNAS HAM which notes that polygamous marriages are vulnerable to neglect of family needs and livelihoods, they fall into the category of domestic violence in the form of economic neglect. Criminal sanctions against polygamy that violate the legal provisions in the three applicable regulations above, can be in the form of: (1) the threat of imprisonment for five to seven years for men who marry even though their marriage has existed before which becomes a legal barrier. ; (2) a maximum imprisonment of 3 months or a maximum fine of Rp. 7,500. ; (3) imprisonment for a maximum of 3 (three) years or a fine of a maximum of Rp. 9,000,000.00 (nine million rupiahs) and or a maximum imprisonment of 4 (four) months or a maximum fine of Rp. 3,000,000.00 (three million rupiah). Keyword: Poligamy, Criminalization, Criminal sanctions.